Effective design of managed realignment schemes can reduce coastal flood risks. (5th September 2020) - Kiesel, Joshua; Schuerch, Mark; Christie, Elizabeth K.; Möller, Iris; Spencer, Tom; Vafeidis, Athanasios T.
Abstract: Managed realignment (MR) constitutes a form of nature-based adaptation to coastal hazards, including sea level rise and storm surges. The implementation of MR aims at the (re)creation of intertidal habitats, such as saltmarshes, for mitigating flood and erosion risks and for creating more natural shorelines. However, some evidence suggests that the desired coastal protection function of MR schemes (in terms of high water level (HWL) attenuation) may be limited and it was hypothesized that this was due to the configuration of the remaining seawalls, which we refer to as scheme design. Here we present the results of a hydrodynamic model application, which we used to analyse the effects of scheme design on within-site HWL attenuation by applying six scheme designs that differ in terms of breach characteristics and water storage capacity. In specific, we vary the configuration of the seaward defence line (including the seawall breaches) and the position of the landward dike by modifying the digital elevation model of the site. Our results show that changes in scheme design, particularly storage area and number and width of breaches, had significant effects on the site's HWL attenuation capacity. Decreasing the tidal prism by changing the number and size of breaches, with the site area kept constant, leads to increased modelled HWL attenuation rates. However, average HWL attenuation rates of >10 cm km −1 are only achieved when site size increases. The mean high water depth of each scheme design scenario, calculated by dividing tidal prism by MR area, explains most of the variation in average HWL attenuation between all scenarios. Attention to potential within-site hydrodynamics at the design stage will aid the construction of more effective MR schemes with respect to coastal protection in the future. Highlights: Breach design and size of managed realignment sites affect high water attenuation. Approximate doubling of site size can elevate average attenuation rates ca. 16-fold. Mean high water depth explains most variation in within-site attenuation rates.